Dual Role of LldR in Regulation of the lldPRD Operon, Involved in l-Lactate Metabolism in Escherichia coli - Aguilera, Laura (American Society for Microbiology (ASM), 2008)
The lldPRD operon of Escherichia coli, involved in l-lactate metabolism, is induced by growth in this compound. We experimentally identified that this system is transcribed from a single promoter with an initiation site located 110 nucleotides upstream of the ATG start codon. On the basis of computational data, it had been proposed that LldR and its homologue PdhR act as regulators of the lldPRD operon. Nevertheless, no experimental data on the function of these regulators have been reported so far. Here we show that induction of an lldP-lacZ fusion by l-lactate is lost in an ΔlldR mutant, indicating the role of LldR in this induction. Expression analysis of this construct in a pdhR mutant ruled out the participation of PdhR in the control of lldPRD. Gel shift experiments showed that LldR binds to two operator sites, O1 (positions −105 to −89) and O2 (positions +22 to +38), with O1 being filled at a lower concentration of LldR. l-Lactate induced a conformational change in LldR that did not modify its DNA binding activity. Mutations in O1 and O2 enhanced the basal transcriptional level. However, only mutations in O1 abolished induction by l-lactate. Mutants with a change in helical phasing between O1 and O2 behaved like O2 mutants. These results were consistent with the hypothesis that LldR has a dual role, acting as a repressor or an activator of lldPRD. We propose that in the absence of l-lactate, LldR binds to both O1 and O2, probably leading to DNA looping and the repression of transcription. Binding of l-lactate to LldR promotes a conformational change that may disrupt the DNA loop, allowing the formation of the transcription open complex.